Effects of Temperature Stress and Aquarium Conditions on the Red Macroalga Delisea pulchra and its Associated Microbial Community - Zozaya-Valdés, Enrique; Roth-Schulze, Alexandra J.; Thomas, Torsten (Frontiers in Microbiology, 2016)
In recent years there has been an increase in the rate and severity of diseases affecting habitat-forming marine organisms, such as corals, sponges and macroalgae. Delisea pulchra is a temperate red macroalga that suffers from a bleaching disease that is more frequent during summer, when seawater temperatures are elevated and the alga’s chemical defense is weakened. A bacterial cause for the disease is implied by previous studies showing that some isolated strains can cause bleaching in vitro and that host-associated microbial communities are distinct between diseased and healthy individuals. However, nothing is known about the successional events in the microbial community that occur during the development of the disease. To study this aspect in the future, we aimed here to develop an experimental setup to study the bleaching disease in a controllable aquarium environment. Application of a temperature stress (up to 27° C) did not cause a clear and consistent pattern of bleaching, suggesting that temperature alone might not be the only or main factor to cause the disease. The results also showed that the aquarium conditions alone seem to be sufficient to produce bleaching symptoms. Microbial community analysis based on 16S rRNA gene fingerprinting and sequencing showed significant changes after 15 days in the aquarium, indicating that the native microbial associates of D. pulchra are not stably maintained. Microbial taxa that were enriched in the aquarium-held D. pulchra thalli, however did not match on a taxonomic level those that have been found to be enriched in natural bleaching events. Together our observations indicate that environmental factors, other than the ones investigated here, might drive the bleaching disease in D. pulchra and that the aquarium conditions have substantial impact on the algal-associated microbiome.